Preliminary Results of the Adoption and Application of the Integrated Comprehensive Care Bundle Care Program When Treating Patients with Chronic Obstructive Pulmonary Disease - Jason R. Guertin; James M. Bowen; Carolyn Gosse; Gord Blackhouse; Daria J. O’Reilly; Emanuel Baltaga; Gerard Cox; Donna Johnson; Brandi Le Blanc; Jane Loncke; Stewart Pugsley; Ravi Sivakumaran; et al. (Canadian Respiratory Journal)
Background. St. Joseph’s Health System has implemented an integrated comprehensive care bundle care (ICC) program with the hopes that it would improve patients’ care while reducing overall costs. The aim of this analysis was to evaluate the performance of the ICC program within patients admitted with chronic pulmonary obstructive disease (COPD). Methods. We conducted a retrospective observational cohort study comparing ICC patients to non-ICC patients admitted to St. Joseph’s Healthcare Hamilton for COPD being discharged with support services between June 2012 and March 2015, using administrative data. Confounding adjustment was achieved through the use of propensity score matching. Medical resource utilizations during the initial hospitalization and within the 60 days following discharge were compared using regression models. Results. All 76 patients who entered the ICC program (100.0%) were matched 1 : 1 to 76 eligible non-ICC patients (28.4%). Length of stay (6.47 [7.29] versus 9.55 [10.21] days) and resource intensity weights (1.16 [0.80] versus 1.64 [1.69]) were lower in the ICC group within the initial hospitalization but, while favoring the ICC program, healthcare resource use tended not to differ statistically following discharge. Interpretation. The ICC program was able to reduce initial medical resource utilization without increasing subsequent medical resource use.